On start-up costs of thermal power plants in markets with increasing shares of fluctuating renewables - Wolf-Peter Schill; Michael Pahle; Christian Gambardella (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The emerging literature on power markets with high shares of fluctuating renewables suggests that more frequent start-up procedures of thermal power plants may become an increasing concern, both for costs and possibly also for market design. Based on official scenario assumptions, we investigate how start-ups and related costs develop in Germany, where the share of fluctuating renewables quadruples between 2010 and 2030. We find that the overall number of start-ups decreases by a third, while related costs increase by half. The relative share of start-up costs in overall variable costs of thermal plants grows only slightly and remains below 1%. Several overlapping effects drive these results. The expansion of fluctuating renewables alone would strongly increase start-up costs. In contrast, increased flexibility of biomass power plants, additional power storage and larger block sizes have opposite effects. While the relevance of start-up costs grows only moderately under baseline assumptions, it may increase further under alternative developments of system flexibility. Future power market design reforms should thus aim to ensure proper remuneration of quasi-fixed start-up costs. Our findings are also relevant for many other countries with thermal power systems that plan to undergo comparable transitions toward fluctuating renewables.
Keywords: Q41; Q47; 330; power sector modeling; start-up costs; unit commitment; renewables